If it's not what You are looking for type in the equation solver your own equation and let us solve it.
D( x )
x = 0
x = 0
x = 0
x in (-oo:0) U (0:+oo)
(4*x-(4/x)-7)*(3*x+5/x-1) = 0
(4*x-4*x^-1-7)*(3*x+5/x-1) = 0
(4*x-4*x^-1-7)*(3*x+5*x^-1-1) = 0
4*x-4*x^-1-7 = 0
4*x^1-4*x^-1-7*x^0 = 0
(4*x^2-7*x^1-4*x^0)/(x^1) = 0 // * x^2
x^1*(4*x^2-7*x^1-4*x^0) = 0
x^1
4*x^2-7*x-4 = 0
4*x^2-7*x-4 = 0
DELTA = (-7)^2-(-4*4*4)
DELTA = 113
DELTA > 0
x = (113^(1/2)+7)/(2*4) or x = (7-113^(1/2))/(2*4)
x = (113^(1/2)+7)/8 or x = (7-113^(1/2))/8
x in { (7-113^(1/2))/8, (113^(1/2)+7)/8}
(x-((7-113^(1/2))/8))*(x-((113^(1/2)+7)/8)) = 0
3*x+5*x^-1-1 = 0
3*x^1+5*x^-1-1*x^0 = 0
(3*x^2-1*x^1+5*x^0)/(x^1) = 0 // * x^2
x^1*(3*x^2-1*x^1+5*x^0) = 0
x^1
3*x^2-x+5 = 0
3*x^2-x+5 = 0
DELTA = (-1)^2-(3*4*5)
DELTA = -59
DELTA < 0
x in { }
1 = 0
(x-((7-113^(1/2))/8))*(x-((113^(1/2)+7)/8)) = 0
( x-((113^(1/2)+7)/8) )
x-((113^(1/2)+7)/8) = 0 // + (113^(1/2)+7)/8
x = (113^(1/2)+7)/8
( x-((7-113^(1/2))/8) )
x-((7-113^(1/2))/8) = 0 // + (7-113^(1/2))/8
x = (7-113^(1/2))/8
x in { (113^(1/2)+7)/8, (7-113^(1/2))/8 }
| 5n=53.2-2.6n | | 10+.06x=0 | | 11=7+4w | | 7y+8/2=4 | | 60+60+x+x=360 | | -8+4v=16 | | 60+60+x+x= | | 4+4-e=2 | | 68+65+x+x= | | 5x+5=10x-3 | | -10x^2+50x+12=0 | | 3n+5x=6 | | .5(8*12)= | | 1/2(2x-5)=3 | | .5(10*12.8)= | | -16X^2+4X+20=0 | | 14x+35=(4x-9)-x | | 10(12.8)= | | 4x+28=13x-93 | | 11x-11=100 | | 9(t+1)=81 | | 3(H+5)=22 | | -2=v-6+3 | | 7x+8/2+4x-3/6=34 | | 0=(1/5)x+2 | | e-5+7=2 | | e/5+7=4 | | 16+3/4x=7 | | 3x^(4/3)+3=51 | | 2/d+1/4=11/12 | | 3x=(124+1676+3600)/2x | | (5a^2)-(6a)-32=0 |